Antioxidant Gel from Brown Algae (Ascophyllum nodosum) and Binahong Leaves for Diabetic Wound Healing - Rahmadianti, Salma; Sofianty, Irine; Aslamiah, Lisa; Insan, Febrian Khoirul; Sihombing, Maria Engzelita; Nuraini, Vidia Afina; Hernawati, Hernawati (Faculty of Medicine Universitas Padjadjaran, 2023)
Background: Diabetic wounds are difficult to treat, causing persistent infections and often leading to limb amputation. One convenient way to manage diabetic wounds is by applying wound dressings. This study aimed to develop a wound dressing in form of a gel containing brown algae and binahong leaf extract for diabetic wound dressings.Methods: This study was an experimental study conducted in the Organic Chemistry Laboratory of Universitas Pendidikan Indonesia from June to September 2022. As many as 33 mice induced by alloxan were divided into 9 groups consisting of application of brown algae extract gel, binahong lead extract gel and a mixture of brown algae, and binahong leaf extract gel with the concentration of 2.5%, 5%, and 10% respectively. All treatments were given within 7 days. Laboratory data collected included phytochemical screening, total phenolic compound, antioxidant activity and organoleptic test.Results: Brown algae and binahong leaf extracts had a high total phenolic content of 331.25 mg GAE/g and 207.01 mg GAE/g, respectively with antioxidant activity of IC50 = 327.33 µg/mL and 209.30 µg/mL, respectively. It was found that brown algae and binahong leaf extracts could accelerate wound closure in a diabetic mouse model. Gel formulation with 10% w/w brown algae extracts presented 91.66% of wound closure, two times greater than treatment with commercial drugs.Conclusion: The developed gel containing brown algae and binahong leaf extracts can be a promising wound dressing for healing diabetic wounds.